Why does a cooled object feel heavier? Psychophysical investigations into the Weber's Phenomenon. Issue 1 (December 2017) - Dunn, James; Mahns, David; Nagi, Saad
Abstract Background It has long been known that a concomitantly cooled stimulus is perceived as heavier than the same object at a neutral temperature—termedWeber's Phenomenon (WP). In the current study, we re-examined this phenomenon using well-controlled force and temperature stimuli to explore the complex interplay between thermal and tactile systems, and the peripheral substrates contributing to these interactions. A feedback-controlled apparatus was constructed using a mechanical stimulator attached to a 5- × 5-mm thermode. Force combinations of 0.5 and 1 N (superimposed on 1-N step) were applied to the ulnar territory of dorsal hand. One of the forces had a thermal component, being cooled from 32 to 28 °C at a rate of 2 °C/s with a 3-s static phase. The other stimulus was thermally neutral (32 °C). Participants were asked to report whether the first or the second stimulus was perceivedheavier . These observations were obtained in the all-fibre-intact condition and following the preferential block of myelinated fibres by compression of ulnar nerve. Results In normal condition, when the same forces were applied, all subjects displayed a clear preference for the cooled tactile stimulus as being heavier than the tactile-only stimulus. The frequency of this effect was augmented by an additional ~17% when cooling was applied concurrently with the second stimulus. Following compression block, the mean incidence of WP was significantly reduced regardless of whether cooling was applied concurrently with the first or the second stimulus. However, while the effect was abolished in case of former (elicited in <50% of trials), the compression block had little effect in four out of nine participants in case of latter who reported WP in at least 80% of trials (despite abolition of vibration and cold sensations). Conclusions WP was found to be a robust tactile–thermal interaction in the all-fibre-intact condition. The emergence of inter-individual differences during myelinated block suggests that subjects may adopt strategies, unbeknownst to them, that focus on the dominant input (myelinated fibres, hence WP abolished by block) or the sum of convergent inputs (myelinated and C fibres, hence WP preserved during block) in order to determine differences in perceived heaviness.